2018
DOI: 10.1111/eff.12459
|View full text |Cite
|
Sign up to set email alerts
|

Radioisotope and stable isotope ratios (Δ14C, δ15N) suggest larval lamprey growth is dependent on both fresh and aged organic matter in streams

Abstract: Lampreys have a complex life cycle which includes a multi‐year infaunal larval stage (ammocoete). Gut content analysis has generally identified detritus (i.e., unidentifiable organic matter) as the major dietary component to ammocoetes, though algae can also be important. However, gut content preserves only a snapshot of the animal's diet and does not reflect assimilated material. In order to better characterise the nutritional sources supporting ammocoete growth, we analysed ammocoete body tissue and potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
1
9
1
Order By: Relevance
“…We performed lipid treatment a priori and included hydrogen isotope analysis in our study in an attempt to overcome this, which may account for the difference in results between studies. A subsequent re‐analysis of the systems tested by Evans and Bauer () which accounted for potential lipid effects and also included radiocarbon as an additional tracer indicated that the earlier study may have overestimated the contribution of autochthonous materials to larval P. marinus (Evans et al ., ), lending further weight to our conclusions.…”
Section: Discussionsupporting
confidence: 78%
“…We performed lipid treatment a priori and included hydrogen isotope analysis in our study in an attempt to overcome this, which may account for the difference in results between studies. A subsequent re‐analysis of the systems tested by Evans and Bauer () which accounted for potential lipid effects and also included radiocarbon as an additional tracer indicated that the earlier study may have overestimated the contribution of autochthonous materials to larval P. marinus (Evans et al ., ), lending further weight to our conclusions.…”
Section: Discussionsupporting
confidence: 78%
“…Lampreys exhibit a multiyear larval stage, which is thought to be biologically and ecologically similar among species (Dawson et al 2015; Docker and Potter 2019). Biologically, all species of lamprey burrow in substrates of freshwater environments and they filter‐feed on algae, bacteria, and organic detritus of aquatic and terrestrial origin during the larval life stage (Dawson et al 2015; Evans et al 2019). As a result of burrowing and feeding activities, larval lampreys are ecologically similar among species in that they can alter the physical and chemical environment of the benthos (Shirakawa et al 2013; Boeker and Geist 2016; Nika et al 2021), leading Shirakawa et al (2013) to suggest that declines in abundance and distribution of larval lampreys in freshwater habitats could diminish overall ecosystem function.…”
Section: Introductionmentioning
confidence: 99%
“…In estuarine ecosystems, organic matter of terrestrial origin is a major contributor to allochthonous organic matter (Duan et al, 2014;Lu et al, 2013). Analysis of the carbon and nitrogen stable isotopic compositions of estuarine organic matter can identify their contributions to the food web (Darnaude et al, 2004;Evans et al, 2019). Generally, POM in estuaries is composed of river POM (mixture of terrestrial POM and freshwater phytoplankton), estuarine-produced and marine phytoplankton, resuspended microphytobenthos and diverse detritus (e.g.…”
Section: Fish Isotopic Nichesmentioning
confidence: 99%